2012
DOI: 10.1177/0961000611434999
|View full text |Cite
|
Sign up to set email alerts
|

Using assignment data to analyse a blended information literacy intervention: A quantitative approach

Abstract: The purpose of this research was to determine whether a blended approach to delivering an information literacy learning and teaching intervention (a mix of face-to-face and online activities) could statistically significantly enhance undergraduate's information discernment compared to standard face-to-face delivery.Three interventions were designed to develop the information literacies of first-year undergraduates studying Sport & Exercise at Staffordshire University. The experimental intervention took a blend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 30 publications
3
41
0
3
Order By: Relevance
“…Findings were mixed for the ten studies that included a blended delivery arm (Anderson & May, 2010;Beile & Boote, 2005;Byerley, 2005;Churkovich & Oughtred, 2002;Goates et al, 2016;Greer et al, 2016;Kraemer et al, 2007;Orme, 2004;Walton & Hepworth, 2012;Wilcox Brooks, 2014), although seven of these studies (70%) found no statistically significant difference between blended and other formats in terms of test or assignment outcomes. Of the ten, one study (Byerley, 2005) noted that the blended method provided greater skill development than the face-to-face provision, although this was not significant compared to online provision.…”
Section: Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings were mixed for the ten studies that included a blended delivery arm (Anderson & May, 2010;Beile & Boote, 2005;Byerley, 2005;Churkovich & Oughtred, 2002;Goates et al, 2016;Greer et al, 2016;Kraemer et al, 2007;Orme, 2004;Walton & Hepworth, 2012;Wilcox Brooks, 2014), although seven of these studies (70%) found no statistically significant difference between blended and other formats in terms of test or assignment outcomes. Of the ten, one study (Byerley, 2005) noted that the blended method provided greater skill development than the face-to-face provision, although this was not significant compared to online provision.…”
Section: Skillsmentioning
confidence: 99%
“…Of the 33 studies, 8 did not include a pretest (Alexander & Smith, 2001;Burhanna et al, 2008;Goates et al, 2016;Greer et al, 2016;Orme, 2004;Schilling, 2012;Silver & Nickel, 2007;Walton & Hepworth, 2012). The remaining 25 studies all noted an increase in skills from pretest to posttest across delivery formats.…”
Section: Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilim ve teknolojinin üretildiği yerler olan yüksek öğretim kurumlarında, bu kurumların idari, kütüphane ve öğretim ortamlarındaki hizmetlerin iyileştirilmesinde teknolojinin kullanılması ise çok hızlı bir şekilde gerçekleşmiştir. Bilgi okuryazarlığı kavramı iletişim teknolojilerinin gelişmesiyle birlikte farklı bir boyut kazanmış ve bu alandaki çalışmalar büyük bir ivme kazanmıştır (Kasowitz-Scheer & Pasqualoni, 2002;Akkoyunlu & Kurbanoğlu, 2003;Walton & Hepworth, 2012;Chu, & Du, 2012). Mevcut araştırmalar bilgi okuryazarlığı öz-yeterlik algısında cinsiyet, yaş, bilgisayar sahipliği, sınıf seviyesi gibi faktörleri incelemiştir (Kurbanoğlu & Akkoyunlu, 2002;Akkoyunlu & Kurbanoğlu, 2003;Akkoyunlu & Kurbanoğlu, 2004;Kahyaoğlu, 2011).…”
Section: Tartişma Ve öNeri̇lerunclassified
“…Üniversite eğitimi almakta olan öğrencilerin bilgi okuryazarlığı öz-yeterlik algılarının araştırılması, onların eğitimleri sırasında dikkat edilmesi gereken unsurları ortaya çıkartabilme açısından önemlidir (Walton & Hepworth, 2012). Bu makale kapsamında bilgi okuryazarlığı öz-yeterlik algısı, üniversite öğrencilerinin ihtiyaçları olan bilgiyi araması, bulması, değerlendirmesi ve kullanması sürecini başarılı olarak geçirebileceklerine yönelik kendileri ile ilgili yargıları olarak kullanılmaktadır (Bandura, 1977;ACRL, 2006).…”
Section: Introductionunclassified